2017
DOI: 10.1177/0897190017738916
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Students and Pharmacy Technicians in Medication Reconciliation: A Review of the Current Literature

Abstract: These findings suggest that pharmacy students and technicians are accurate, time efficient, decrease costs, and provide support to other health-care professionals when they are included in the medication reconciliation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 32 publications
4
20
0
Order By: Relevance
“…To our knowledge, this is the first study to evaluate the clinical and inter-professional learning possibilities of interprofessional student teams working together to review the medications of patients attending an outpatient clinic. Similar to other studies that focused on IPE, we also found that the students gained an understanding of other health professionals' capabilities [9,16,17]. Since previous studies have shown that healthcare students can actively be involved in taking medication histories and/or giving medication advice [16,18], our study is the first to show that a trained inter-professional student team can perform all the steps of a full medication review.…”
Section: Discussionsupporting
confidence: 83%
“…To our knowledge, this is the first study to evaluate the clinical and inter-professional learning possibilities of interprofessional student teams working together to review the medications of patients attending an outpatient clinic. Similar to other studies that focused on IPE, we also found that the students gained an understanding of other health professionals' capabilities [9,16,17]. Since previous studies have shown that healthcare students can actively be involved in taking medication histories and/or giving medication advice [16,18], our study is the first to show that a trained inter-professional student team can perform all the steps of a full medication review.…”
Section: Discussionsupporting
confidence: 83%
“…Methods that may be employed might include use of information technology, the use of verbal or pictographic information exchange, education of family members or caregivers, or the use of other educational resources or healthcare team members. 31,32 Clinicians and healthcare staff need to have a high level of awareness to detect and address low health literacy, medication errors and reconciliation problems.…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacy student-assisted medication reconciliation: Number and types of medication discrepancies identified by pharmacy students medication history during admission and identify discrepancies. [12][13][14][15][16] In the US, one study showed that 11 PharmD students identified 922 discrepancies when conducting medication reconciliation in 330 patients in three hospitals. 14 Furthermore, pharmacy students from the US and Canada have also been shown to obtain more accurate medication histories than fully trained nurses and physicians.…”
Section: Original Researchmentioning
confidence: 99%
“… 9 Despite clear benefits, many hospitals have reported that they are unable to provide this service to all patients due to workforce limitations and competing priorities for hospital pharmacists. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%